0098 Evaluation of sleep problems and sleep hygiene for shift workers in korean steel manufacturing company. (21st August 2017) - Lee, Ji-Won; Kim, Hyoung-Ryoul; Jang, Taewon; Lee, Hye-Eun; Byun, Junsu; Lee, Seyoung
Abstract : Objectives: To estimate self-reported sleep health of shift workers and construct plans to minimise harm of the shiftwork. Methods: A cross-sectional survey was conducted by using structured questionnaires on workers who were employed in a steel company. They divided into 3 groups (daytime workers, 4 teams 3 shifts, and other shifts). The survey contains questionnaires about demographic characteristics, sleep hygiene, condition of their work place, Insomnia Severity Index (ISI) and the Epworth Sleepiness Scale (ESS) to evaluate workers' sleep disorder and daytime sleepiness. Among shift-workers, 'insomnia group' is compared to 'normal sleep group' with chi-square test. The multiple logistic regression analysis was performed to explore risk factors of 'severe insomnia'. Results: Workers with severe insomnia were 6.7% in other shifts group, and 2.3% in 4 teams 3 shifts group. There was no severe insomnia in daytime workers. Among 4 teams 3 shifts group, 12.9% workers complained severe daytime sleepiness. With the practice of sleep hygiene, generally the items for improving environment to sleep well showed higher rate in 'severe insomnia group' than 'normal sleep group'. It might be that the workers who suffered from insomnia tried to overcome it. The items which disrupt sleep were concordantly higher in 'insomnia group' than in 'normal sleep group', suggesting that such kind of adverse sleep habits are negatively affect sleep of shift workers. Conclusion: The results of present study suggest relationship between sleep hygiene and sleep disorders among shift workers. To minimise shift worker's sleep problem, proper sleep hygiene is necessary.